The Child Affective Facial Expression Set Short Versions (CAFE-Ss): Development and Validation of Two Subsets of Children’s Emotional Faces With Variability - Yang, Yang; LoBue, Vanessa (Frontiers in Psychology, 2020)
Emotion recognition plays an important role in children’s socio-emotional development. Research on children’s emotion recognition has heavily relied on stimulus sets of photos of adults posed stereotyped facial configurations. The Child Affective Facial Expression set (CAFE) is a relatively new stimulus set that provides researchers with photographs of a diverse group of children’s facial configurations in seven emotional categories—angry, sad, happy, fearful, disgusted, surprised, and neutral. However, the large size of the full CAFE set makes it less ideal for research in children. Here, we introduce two subsets of CAFE with 140 photographs of children’s facial configurations in each set, diverse in the race and ethnicity of the models, and designed to produce variability in naïve observers. The subsets have been validated with 1000 adult participants.